Performance analysis of industrial steam turbines used as air expander in Compressed Air Energy Storage (CAES) systems - Ambra Giovannelli; Luca Tamasi; Coriolano Salvini (Energy Reports, 2020)
The Authors consider that as a mid-term storage technology (from some hours to some days), small/medium size CAES systems (1-10 MW) might be efficiently and profitably used for off-grid and self-consumption applications as well as for the provision of ancillary services on the lower grid levels. A crucial aspect related to the feasibility of the system concerns with the availability of efficient and affordable air expanders. For typical applications, suitable values for pressure at the air expander inlet range from 40 to 60 bar. Since such values are comparable with those featuring industrial steam turbines, an interesting option to reduce development efforts and costs is to take as a reference the common steam turbine engineering practice. The goal of the present paper is to explore the possibility of using existing modules developed by industrial steam turbines manufacturers to assemble the air expander. On the basis of available information, a possible arrangement for an air turbine has been set up and modeled. Results show a loss of performance in terms of efficiency in respect to steam operations. Nevertheless, the performance level in a really wide range of operation can be considered more than satisfactory. Therefore, the use of industrial steam turbines technology might be considered of interest for the intended applications.
Keywords: 330; Air expander; Compressed Air Energy Storage (CAES); Industrial steam turbines; Turbomachinery modeling